2015
DOI: 10.1080/15374416.2015.1004680
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Correlates of Sluggish Cognitive Tempo and ADHD-Inattention Symptom Dimensions with Spanish Children

Abstract: The objective was to examine the longitudinal correlates of sluggish cognitive tempo (SCT) and attention deficit/hyperactivity disorder (ADHD)-Inattention (IN) dimensions with mothers' and fathers' ratings of Spanish children. Mothers and fathers rated SCT, ADHD-IN, ADHD-hyperactivity/impulsivity (HI), oppositional defiant disorder (ODD), depression, academic impairment, and social impairment on 3 occasions (twice in first-grade year [6-week separation] and once in the second-grade year [12 months after the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
65
1
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 9 publications
12
65
1
14
Order By: Relevance
“…Still, mixed findings have been reported. For instance, several studies have not found SCT to be associated with academic difficulties after controlling for ADHD symptoms (e.g., Bauermeister et al 2012;Becker and Langberg 2013;Carlson and Mann 2002), whereas other studies have found SCT to remain associated with poorer academic functioning after controlling for ADHD (e.g., Becker et al 2014b;Bernad et al 2014;Burns et al 2013;Langberg et al 2014;Lee et al 2014;Servera et al 2015;Willcutt et al 2014). Interestingly, findings from one recent study suggest that SCT may relate to impairment according to parent ratings but not according to teacher ratings (Watabe et al 2014).…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Still, mixed findings have been reported. For instance, several studies have not found SCT to be associated with academic difficulties after controlling for ADHD symptoms (e.g., Bauermeister et al 2012;Becker and Langberg 2013;Carlson and Mann 2002), whereas other studies have found SCT to remain associated with poorer academic functioning after controlling for ADHD (e.g., Becker et al 2014b;Bernad et al 2014;Burns et al 2013;Langberg et al 2014;Lee et al 2014;Servera et al 2015;Willcutt et al 2014). Interestingly, findings from one recent study suggest that SCT may relate to impairment according to parent ratings but not according to teacher ratings (Watabe et al 2014).…”
mentioning
confidence: 91%
“…Although an agreed-upon symptom set for SCT remains to be established (Becker 2013), research increasingly indicates that SCT and attention-deficit/hyperactivity disorder inattention (ADHD-IN) symptoms represent different dimensions of psychopathology (Barkley 2013;Becker et al 2014b;Bernad et al 2014;Burns et al 2013;Fenollar Cortés et al 2014;Garner et al 2014;Lee et al 2014;McBurnett et al 2014;Penny et al 2009). It is also evident that SCT is distinct from internalizing symptoms of anxiety and depression (Becker et al 2014d;Lee et al 2014;Servera et al 2015;Willcutt et al 2014). Moreover, although it remains unclear whether or not SCT is uniquely associated with processing speed (Bauermeister et al 2012;Willcutt et al 2014), it is important to note that SCT is either unassociated with intelligence (Becker and Langberg 2013;Skirbekk et al 2011) or may even be associated with higher levels of intelligence in children with ADHD (Marshall et al 2014).…”
mentioning
confidence: 96%
See 3 more Smart Citations